Mechanisms of Bone Resorption in Periodontitis - Stefan A. Hienz; Sweta Paliwal; Saso Ivanovski (Journal of Immunology Research)
Alveolar bone loss is a hallmark of periodontitis progression and its prevention is a key clinical challenge in periodontal disease treatment. Bone destruction is mediated by the host immune and inflammatory response to the microbial challenge. However, the mechanisms by which the local immune response against periodontopathic bacteria disturbs the homeostatic balance of bone formation and resorption in favour of bone loss remain to be established. The osteoclast, the principal bone resorptive cell, differentiates from monocyte/macrophage precursors under the regulation of the critical cytokines macrophage colony-stimulating factor, RANK ligand, and osteoprotegerin. TNF-α, IL-1, and PGE2 also promote osteoclast activity, particularly in states of inflammatory osteolysis such as those found in periodontitis. The pathogenic processes of destructive inflammatory periodontal diseases are instigated by subgingival plaque microflora and factors such as lipopolysaccharides derived from specific pathogens. These are propagated by host inflammatory and immune cell influences, and the activation of T and B cells initiates the adaptive immune response via regulation of the Th1-Th2-Th17 regulatory axis. In summary, Th1-type T lymphocytes, B cell macrophages, and neutrophils promote bone loss through upregulated production of proinflammatory mediators and activation of the RANK-L expression pathways.